Laron Syndrome - From Man to Mouse Lessons from Clinical and Experimental Experience - Laron, Zvi.; Kopchick, J.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
Laron syndrome (LS), or primary growth hormone (GH) insensitivity, was first described in 1966. Since then, many patients worldwide have been diagnosed with LS, which involves defects in the GH receptor that cause combined congenital deficiency of GH and IGF-I activities. In this comprehensive book the authors draw upon 50 years of multidisciplinary clinical and investigative follow-up of the large Israeli cohort of LS patients. The genetic basis of the syndrome is fully considered, and all aspects of the pathophysiology of IGF-I deficiency are described. Data derived from the recently generated mouse model of LS are reviewed and compared with the human LS experience. Valuable advice is provided on treatment, and treatment effects, such as metabolic effects, adipose tissue alterations, and impact on aging, are fully explored. Together, this book condenses, consolidates, compares, and contrasts data derived from the human and mouse LS experiences and provides a unique resource for clinical and basic scientists to evaluate and compare IGF-I and GH actions.
From the Content: Part I - Laron Syndrome in Man -- Clinical Aspects -- History of the Israeli Cohort of Laron Syndrome Patients -- Early Investigations -- Clinical Evidence of Growth Hormone Resistance in Patients with Laron Syndrome -- Diagnosis of Laron Syndrome -- Genetic Aspects -- Clinical Evaluation -- Perinatal Evaluation -- Perinatal Development ;Laron Syndrome -- Linear Growth Pattern of Untreated Laron Syndrome Patients -- Head Shape, Size and Growth of Untreated Patients with Laron Syndrome -- Sexual Development in Patients with Laron Syndrome.
Keywords: Medicine; Human genetics; Human physiology; Internal medicine; Endocrinology; Pediatrics; Medicine & Public Health; Pediatrics; Endocrinology; Internal Medicine; Human Genetics; Molecular Medicine; Human Physiology